Para entender o repertório linguístico no ensino superior tecnológico: conversa entre a translinguagem e a educação sociocomunitária - Souza, Lilian de (Universidade Federal de São Carlos, 2021)
This thesis presents the results of a research that investigated the role of named languages in Spanish learning, supported by translingual practices and socio-community education. The investigation took place in a context of teaching languages for specific purposes, in the Spanish class, inserted in the higher course of Events (formation of the Tourism, Hospitality and Leisure axis, acting in the organization and execution of events), at the Faculty of Technology of the State of São Paulo. The researcher observed, in foreign language classes, the incidence of the use of Portuguese during the activities, as well as other languages that are part of the linguistic repertoire of the students, thus, the Translanguaging theory was used in the studies developed by Canagarajah (2011) García (2014) and Li Wei (2017), who recognize the linguistic repertoire that each individual has to communicate, in a movement that transposes the languages with which they have contact, in order to make themselves understand and understand the other , regardless of the named language used. To help in the quest to understand the adaptations and uses of each subject's repertoire, Social and Community Education was used, which according to Bissoto (2012, 2016), Groppo (2013), Gomes (2008), Antônio (2012) and Miranda (2016) it is understood as a process of listening to different voices that configure the subjects, in an articulation between teaching and community, a socializing education. Translanguaging and Sociocommunity Education can compose a new discussion on education, as both highlight the need for the participation of the family and the community in the construction of knowledge, aiming at a society of greater equity. The research sought to investigate the role of the linguistic repertoire in Spanish learning from the perspective of translingual practices and socio-community education, in order to know how and at what time Brazilian students resort to the use of their mother tongue and/or other languages in the context of teaching languages for specific purposes, in addition to what would be the students' own perception of this phenomenon. The study follows an ethnographic-based qualitative methodology, which listens to the voice of all participants through an interview conducted by the researcher, on the analysis of the transcript of the virtual interaction carried out in pairs and which gave rise to the videos that comprised an evaluation activity of the subject. Data generation took place in four stages, namely: i) conducting a conversation in pairs recorded on video and sent to the teacher; ii) transcription of all recordings by the researcher teacher and subsequent return to the respective pairs; iii) reading and notes by students about the transcribed dialogue; iv) individual interview with each participant, in order to know their perceptions about the notes made both by the teacher and by themselves. The results of this investigation allowed a better understanding of the adaptations and the role of the Portuguese language, as well as the other languages that are part of the linguistic repertoire of students involved in foreign language learning.

Esta tese presenta los resultados de un trabajo que investigó el papel de las lenguas nombradas en el aprendizaje de español, apoyada en las practicas translíngues y en la educación sociocomunitária. La investigación ocurrió en un contexto de enseñanza de lenguas para fines específicos, en clase de español, inserida en el curso superior de Eventos (formación del eje de turismo, hospitalidad y entretenimiento, con actuación en la organización y ejecución de eventos), de una institución de enseñanza superior tecnológica. El estudio observó, en las clases de lengua extranjera, la incidencia del uso del portugués al transcurrir de las actividades, bien como de otros idiomas (como inglés y italiano) que hacen parte del repertorio lingüístico de los alumnos, de este modo, acorre a la teoría de la Translenguaje, en los estudios desarrollados por Canagarajah (2011), García (2014) y Li Wei (2017), que reconocen el repertorio lingüístico que cada individuo dispone para comunicarse, en un movimiento que transpone las lenguas con que tiene contacto, con el objetivo de hacerse comprender y comprender el otro, independiente del idioma nombrado utilizado. Para auxiliar en la búsqueda por entender las adaptaciones y los usos del repertorio de cada sujeto, se valió de la Educación Sociocomunitaria, que según Bissoto (2012, 2016), Groppo (2013), Gomes (2008), Antônio (2012) y Miranda (2016) entendida como un proceso de escucha de diferentes voces que configuran los sujetos, en una articulación entre la enseñanza y la comunidad, una educación socializadora. Translenguaje y la Educación Sociocomunitária pueden componer una nueva discusión sobre la educación, pues ambas evidencian la necesidad de la participación de la familia y de la sociedad en la construcción del conocimiento, mirando una mayor equidad. La búsqueda investiga cuál es el papel del repertorio lingüístico en el aprendizaje de español bajo la óptica de las practicas translíngues y de la educación sociocomunitária, de forma a saber como y en qué momento los estudiantes brasileños recurren al uso de la lengua materna / o otras lenguas en el contexto de enseñanza de lenguas para fines específicos, además de cuál seria la percepción de los propios estudiantes sobre ese fenómeno. El estudio sigue una metodología cualitativa de base etnográfica, que escucha la voz de todos los participantes por medio de una entrevista realizada por la pesquisidora sobre el análisis de la transcripción de la interacción virtual realizada en parejas y que originó los videos que compusieron una actividad evaluativa de la asignatura. La generación de los datos ocurrió en cuatro etapas, a saber: i) realización de una charla entre las parejas grabada en video y enviada a la profesora; ii) transcripción de todas las grabaciones por parte de la profesora pesquisidora y posteriormente devolución a las respectivas parejas; iii) lectura y apuntamientos por parte de los alumnos sobre el diálogo transcrito; iv) entrevista individual con cada participante, con la finalidad de conocer sus percepciones sobre dos apuntamientos realizados tanto por la profesora como por los estudiantes. Los resultados de esta investigación que fueron interpretados y analizados permitieron comprender mejor las adaptaciones y el papel de la lengua portuguesa bien como las otras lenguas que forma parte del repertorio lingüístico de los estudiantes involucrados en el aprendizaje de otro idioma.
To understand the linguistic repertoire in technological higher education: a dialogue between translanguaging and socio-community education
Para entender el repertório linguístico en la enseñanza superior tecnológico: charla entre translenguaje y educación sociocomunitária
Keywords: Translinguagem; Educação Sociocomunitária; Ensino de línguas para Fins Específicos; Translanguaging; Sociocommunity education; Professional education; Translenguaje; Educación sociocomunitária; Educación profesional; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA